European Yearbook of International Economic Law 2010
XV, 426 p.
Keywords: The first volume of the new Yearbook tries to catch the broadness of contemporary International Economic Law. In part I, it brings together articles on a variety of subjects, reaching from exchange rate manipulation and financial market supervision over international investment law including the growing investment protectionism to recent developments of the external economic constitution of the European Union and the relationship between climate change and International Economic Law. Part II covers the major regional economic integration developments around the globe, analysed in different articles covering the different regions. Part III informs about recent activities in some of the major global economic institutions.